2014
DOI: 10.1097/icl.0000000000000041
|View full text |Cite
|
Sign up to set email alerts
|

Improving Adherence to National Recommendations for Zoster Vaccination Through Simple Interventions

Abstract: Background In 2011, 15.8% of eligible patients in the US were vaccinated against herpes zoster (HZ). Purpose To increase usage of the HZ vaccine by studying physicians’ knowledge, attitudes, practices, and perceived obstacles after interventions to overcome barriers. Methods General internal medicine (GIM) physicians were surveyed with a cross-sectional internet survey October to December 2011 before interventions to increase use of the HZ vaccine and 1 year later. Interventions included education, increas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 26 publications
0
7
0
Order By: Relevance
“…A study from the Netherlands of prospective candidates for the vaccine found that even when cost was removed as a limiting factor, major barriers to vaccination remained including perceived lack of recommendation by the provider and the perception of low risk for HZ [35]. Interventions including provider education, use of clinical reminders in the electronic medical record, increasing on-site availability and nursing administration of the vaccine have been shown to increase vaccine usage [36]. …”
Section: Ten Years Later Barriers To Vaccination Remainmentioning
confidence: 99%
“…A study from the Netherlands of prospective candidates for the vaccine found that even when cost was removed as a limiting factor, major barriers to vaccination remained including perceived lack of recommendation by the provider and the perception of low risk for HZ [35]. Interventions including provider education, use of clinical reminders in the electronic medical record, increasing on-site availability and nursing administration of the vaccine have been shown to increase vaccine usage [36]. …”
Section: Ten Years Later Barriers To Vaccination Remainmentioning
confidence: 99%
“…Despite interventions to overcome these barriers, including education, availability at pharmacies and electronic medical record reminders, primary-care doctors do not consider this vaccine as important as influenza and pneumonia vaccines 42 43. Ophthalmologists can also recommend this vaccine to their patients 41.…”
Section: The Zoster Vaccinementioning
confidence: 99%
“…One of the main causes of low immunizations rates is attributed to the lack of provider recommendation, albeit time constraints, knowledge deficits, or personal beliefs. 16 The National Vaccine Advisory Committee recommends registering vaccinations in individual state's Immunization Information Systems (IIS) to document and track immunizations 17 as a means to improve awareness and knowledge of required adult immunizations.…”
Section: Descriptionmentioning
confidence: 99%
“…9 In 2015, approximately 69% of the Medicare enrollees signed up for Medicare Part D. 8 Clinicians were not able to administer the vaccine at the clinical appointment due to reimbursement concerns, hampering the ability to offer certain vaccinations. 16 In 2014, the cost for Zostavax® in the United States ranged from $123 to $253. 20 could produce a fee of up to $32 for the clinician.…”
Section: Descriptionmentioning
confidence: 99%
See 1 more Smart Citation